Fetomaternal outcomes in pregnancy complicated by epilepsy: a retrospective study - R., Chithra; Dixit, Siddhi Shree; M. K., Janu; ., Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study is conducted to find out possible course and complications of epilepsy and its treatment in mother and fetus as many women will be anxious regarding this high-risk condition. Methods: This is a retrospective study conducted in department of obstetrics and gynaecology, AIMS Kochi from 2012-2019. Out of a total of 7045 deliveries during that period, we identified 64 patients with epilepsy complicating pregnancy. Antepartum, intrapartum and postpartum details of 57 patients whose data was available in electronic medical records was collected and analysed using SPSS 17 software. Results: In this study we noted that the incidence of epilepsy was 0.009%. the 50% of patients were in 25-30 years age group. More than 98% were on long term antiepileptic drugs. Majority were on monotherapy, most commonly on leviteracetam and were well controlled with monotherapy. The 38.5% had recurrence of seizures during pregnancy, mostly in latter half of pregnancy. Patients with seizure free interval of 9 months prior to pregnancy did not have any further epilepsy episodes. The incidence of other medical and obstetric complications was found to be similar to general population. There was 10% incidence of IUGR and fetal anomaly. Conclusions: The seizures were well controlled with monotherapy and we found that generally pregnancy and delivery is well tolerated and overall neonatal outcomes were good.